Numerical assessment of riverbank filtration using gravel back filter to improve water quality in arid regions - Abd-Elaty, Ismail; Saleh, Osama K.; Ghanayem, Hala M.; Zeleňáková, Martina; Kuriqi, Alban (Frontiers in Earth Science, 2022)
The most significant challenge is facing water resources in high-stress regions, especially in developing countries, is adopting non-traditional methods to obtain safe drinking water in desired amounts. In Egypt, the Riverbank Filtration (RBF) system is one of the most common solutions to solve rivers' water quality issues. Several sites have been investigated, and the system has demonstrated tremendous potential. The drinking water plant in Embaba, Giza, Egypt site is considered in this study to improve the quality of the extracted water. The numerical code of MODFLOW is used to simulate the impact of using the emplacement of the gravel-pack filter (GPF). Three different scenarios were investigated; the first is vertical GPF, the second is horizontal GPF for the geometry of the filter for depths, widths or thickness, lengths, and permeability of the filter material, the third is drilling a pipe filter through the riverbed for the pipe numbers, depths, and material hydraulic conductivity. The results revealed that the rate of Riverbank Filtration Sharing (RBFS) was increased by increasing the filter width or thickness at the riverside, the filter pipe numbers, the length of the horizontal filter, and the permeability of filter material. At the same time, it was decreased by increasing the filter width at the groundwater side, the thickness at the river bed. Also, the RBFS was increased by increasing the filter width or the thickness in the two directions and the pipe length. However, it returned to decrease again due to groundwater sharing. The gravel-pack and pipe filter geometry and permeability impact rate of RBFS, which can be considered in the RBF design.